2010
DOI: 10.1177/112070001002000415
|View full text |Cite
|
Sign up to set email alerts
|

A Reproducible and Inexpensive Method of Measuring Hip Abductor Strength

Abstract: The evaluation of hip abductor strength is useful in assessing of the outcome of hip surgery. Hand-held dynamometers are available, but they are less reliable in assessing hip abductor strength than some other muscle groups. We describe a new device designed to measure hip abductor strength, which is practical in a clinical setting. A system of constraints, pads and reference points was devised to make force measurements as little examiner-dependent as possible. Reproducibility was assessed in a controlled set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The device showed high reproducibility and low uncertainty (within 1 N), previously evaluated with a healthy population. 28…”
Section: Phase 2 (2nd Week)mentioning
confidence: 99%
See 1 more Smart Citation
“…The device showed high reproducibility and low uncertainty (within 1 N), previously evaluated with a healthy population. 28…”
Section: Phase 2 (2nd Week)mentioning
confidence: 99%
“…The device showed high reproducibility and low uncertainty (within 1 N), previously evaluated with a healthy population. 28 Functional outcome measures such as Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), HHS, 10 Metre Walk Test (10 mt WT), and patient satisfaction (12-Item Short-Form Health Survey ) were also used at each follow-up. The assessment was always carried out by the same physical therapist (LC).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…They found high inter-and intra-observer reliability for all devices (ICC 0.88 to 0.95). Ford-Smith et al 16 and Traina et al 17 also found high ICC values for MDD devices (0.73 to 0.98).…”
Section: Resultsmentioning
confidence: 90%
“…Three studies 15 - 17 measured hip muscle strength using MDD. Click Fenter et al 15 compared three commercially available MDD devices when used on a population of ten participants over three separate days.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation